2020
DOI: 10.1016/j.ygyno.2020.09.042
|View full text |Cite
|
Sign up to set email alerts
|

No influence of sarcopenia on survival of ovarian cancer patients in a prospective validation study

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…No observational studies on exercise or sedentary behavior were found. A retrospective study design was used for all but three included studies [ 44 , 45 , 46 ]. Patients with FIGO stage III-IV were included in 39 studies, 30 studies included patients with all stages, 2 studies included FIGO stage I-II, and stage was not specified in 2 other studies.…”
Section: Resultsmentioning
confidence: 99%
“…No observational studies on exercise or sedentary behavior were found. A retrospective study design was used for all but three included studies [ 44 , 45 , 46 ]. Patients with FIGO stage III-IV were included in 39 studies, 30 studies included patients with all stages, 2 studies included FIGO stage I-II, and stage was not specified in 2 other studies.…”
Section: Resultsmentioning
confidence: 99%
“…A measurement error of 2% was used based on previously reported accuracy of CT for muscle and fat tissue analysis [12,28]. Loss/gain of skeletal muscle mass or density was defined as >2% decrease/increase per 100 days, in line with Rutten et al [12] and Ubachs et al [14].…”
Section: Skeletal Muscle Mass and Densitymentioning
confidence: 99%
“…Future studies on prehabilitation programs to lower the risk for postoperative complications could further investigate which patients are prone for muscle density loss, how to prevent decline in skeletal muscle density and whether this is effective in preventing postoperative complications. Furthermore, we used the same method to define loss of skeletal muscle mass and density as the largest of the three currently available studies [12] [e] [14] on CTmeasured changes in body composition among patients treated with NACT for ovarian cancer, facilitating the ability to compare results. Also, all CT measurements were executed by a board certified radiologist with extensive experience [26].…”
Section: Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations